Pregabalin and gabapentin for chronic low back pain without radiculopathy: a systematic review - Rafael Trindade Tatit; Arthur Werner Poetscher; Carlos Augusto Cardim de Oliveira (Arquivos de Neuro-Psiquiatria)
Background Chronic low back pain (CLBP) is a global health problem, and gabapentin and pregabalin are often used in the treatment of patients without associated radiculopathy or neuropathy. Therefore, determining their efficacy and safety is of enormous value. Objective To examine the efficacy and safety of using gabapentin and pregabalin for CLBP without radiculopathy or neuropathy. Methods We performed a search on the CENTRAL, MEDLINE, EMBASE, LILACS, and Web of Science data bases for clinical trials, cohorts, and case-control studies that evaluated patients with CLBP without radiculopathy or neuropathy for at least eight weeks. The data were extracted and inserted into a previously-prepared Microsoft Excel spreadsheet; the outcomes were evaluated using the Cochrane RoB 2 tool, and the quality of evidence, using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Results Of the 2,230 articles identified, only 5 were included, totaling 242 participants. In them, pregabalin was slightly less efficacious than amitriptyline, the combination of tramadol/acetaminophen, and celecoxib, and pregabalin added to celecoxib showed no benefit when compared to celecoxib alone (very low evidence for all). On the other hand, although one study with gabapentin did not support its use in a general sample of patients with low back pain, another found a reduction in the pain scale and improved mobility (moderate evidence). No serious adverse events were observed in any of the studies. Conclusion Quality information to support the use of pregabalin or gabapentin in the treatment of CLBP without radiculopathy or neuropathy is lacking, although results may suggest gabapentin as a viable option. More data is needed to fill this current gap in knowledge.